Analysis of deviation shapes on noise-causing gears - Lyu, Hao; Shi, Zhaoyao; Wang, Shitao (Metrology and Measurement Systems, 2026)
In modern industrial applications, gears serve as pivotal transmission components, whose transmission performance is critical to operational stability of mechanical systems. For electric vehicles subject to stringent noise control specifications, the suppression and control of gear transmission noise carry heightened importance. To tackle gear noise at its root cause, this paper regards gear deviations as the primary excitation source of vibration and noise and systematically analyses six typical gear deviation shapes as well as the corresponding tooth-pair change-over characteristics in meshing. In addition, the mechanism of formation of the corner contact phenomenon and its influential effect on gear transmission errors are being investigated in depth. On this basis, in this paper a novel least-squares sine wave fitting method is proposed. The results demonstrate that the proposed method can effectively achieve the separation and quantitative characterisation of diverse gear deviations. Meanwhile, this paper conducts an in-depth analysis of transmission errors in noise-causing gears, verifying that eccentricity error, pitch deviation and tooth surface texture of gears are the key influencing factors dominating transmission errors and subsequent noise excitation. This research provides a refined analytical paradigm and reliable technical support for the precision quality evaluation and noise fault diagnosis of gears.